InfraNodus analysis of text, networks, and sentiment on a political actor across media platforms - Lawelai, Herman; Nurmandi, Achmad; Maulana, Harry Fajar; Jubba, Hasse (Jurnal Komunikasi, 2025)
This study examines how public perceptions of Anies Baswedan are shaped through YouTube, Twitter, and Google, employing text, network, and sentiment analysis with InfraNodus. Data was collected through each platform's official API with a focus on the keyword "Anies Baswedan." The findings reveal that informative narratives dominate YouTube, while Twitter serves as a space for emotional expression, characterized by a high level of positive sentiment. At the same time, Google reflects information-seeking behavior with a more balanced sentiment distribution. These findings reveal that each platform plays a unique role in shaping political perceptions: YouTube archives and disseminates documentation, and Twitter serves as a forum for debate and support. At the same time, Google functions as an aggregator of opinions from various sources. This study offers new insights into how cross-platform interactions are influenced not only by the content of messages but also by communication patterns and the digital ecosystem in which conversations occur, thereby strengthening our understanding of how political narratives evolve in the digital age.